Longwood area, general view of a private residence at 4 Monmouth Street, Brookline, Massachusetts, 2 of 2. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house in the Longwood area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Longwood Area (2) Residence, 4 Monmouth St. Walking Tour.; Binder Number 4. Pocket Number: 4.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.